The pirate [videorecording (DVD)] - Minnelli, Vincente; Kelly, Gene, 1912-1996; Kelly, Gene, 1912-1996; Garland, Judy; Slezak, Walter, 1902-1983; Behrman, S. N. (Samuel Nathaniel), 1893-1973 (Turner Entertainment Co. : Warner Home Video, 2007)
A Caribbean beauty, who is engaged to a local rich man, has a mad crush on the legendary pirate, Macoco. A traveling singer falls in love with the beauty and to impress her, he poses as the pirate.